Terrorism : a critical introduction - Jackson, Richard, 1967- (Houndmills, Basingstoke, Hampshire ; New York : Red Globe Press, 2011)
"Terrorism has a long history but the devastating attacks of 9/11 transformed what had been seen as a relatively minor security issue into one of major global significance. This incisive new text provides an accessible and balanced assessment of political terror and its study and in the process rethinks many assumptions"--
Machine generated contents note: -- Introduction -- PART I: THE STUDY OF POLITICAL TERRORISM -- The Orthodox Study of Terrorism -- Critical Approaches to Terrorism Studies -- The Cultural Construction of Terrorism -- Bringing Gender into the Study of Terrorism -- PART II: KEY ISSUES -- Conceptualizing Terrorism -- Reconsidering the Terrorism Threat -- Types of Terrorism -- Understanding State Terrorism -- The Causes of Non-State Terrorism -- Responding to Non-State Terrorism -- Assessing the War on Terror.
Includes bibliographical references and index.
ARC
Keywords: Terrorism; Social problems and services